Estudio de pertinencia de un sistema de gestión de calidad para mejorar el proceso de evaluación y acreditación del área de posgrados de la Universidad Nacional de Loja - Villavicencio Canelos, Edgar Oswaldo (2024)
The evaluation and accreditation of higher education institutions is a complex and far-reaching process that is carried out to ensure that an institution meets established standards and provides quality education. Evaluation and accreditation are conducted through a comprehensive analysis of the programs, facilities, resources and services offered by the institution, to determine if they meet the requirements established by the corresponding accreditation body. The graduate area of the National University of Loja (UNL) needs to improve its evaluation and accreditation processes at national and regional level. This is because the institution has been affected by the pressure from other higher education institutions to ensure that their graduate programs are competitive and of high quality. To meet these standards, the university needs to implement a quality management system that allows it to ensure proper evaluation and accreditation for its graduate programs. The objective of this research was to design a quality management system specific to the graduate area of UNL, following the ISO 9001 standard. The methodology was qualitative, using interviews with key stakeholders and document analysis. The results showed the need to implement a comprehensive system to standardize and document procedures, promote an organizational culture of continuous improvement, and facilitate compliance with evaluation and accreditation criteria. The proposed system includes process documentation, flowcharts, quality objectives, and training actions. The research concludes that the implementation of this quality management system would have a significant impact on improving the evaluation and accreditation processes in the graduate area of UNL. Its adoption and staff training are recommended. Keywords: quality management, evaluation, accreditation, higher education, graduate studies